1990
DOI: 10.1111/j.1471-4159.1990.tb01238.x
|View full text |Cite
|
Sign up to set email alerts
|

Cyclic GMP Regulates Nicotine‐Induced Secretion from Cultured Bovine Adrenal Chromaffin Cells: Effects of 8–Bromo–Cyclic GMP, Atrial Natriuretic Peptide, and Nitroprusside (Nitric Oxide)

Abstract: Methacholine, atrial natriuretic peptide (ANP), nitroprusside (nitric oxide), angiotensin II, and bradykinin raised cyclic GMP (cGMP) levels in cultured bovine adrenal chromaffin cells. The role of cGMP in secretion from chromaffin cells was examined using 8-bromo-cGMP. This analogue had no effect on basal secretion or secretion due to angiotensin II, bradykinin, or a high K+ level but potentiated secretion due to low doses of nicotine. At supramaximal doses of nicotine, 8-bromo-cGMP inhibited secretion. These… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
18
3
1

Year Published

1990
1990
2010
2010

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 79 publications
(25 citation statements)
references
References 21 publications
3
18
3
1
Order By: Relevance
“…Moreover, the presence of endothelial cells has been reported to inhibit the K + -induced or the nicotinic receptor agonist DMPP-induced CA secretion in cultured bovine chromaffin cells (Torres et al, 1994), suggesting that not only nNOS but also eNOS may play roles in modulating adrenal CA secretion. In contrast, it has been shown that L-NAME inhibits ACh-induced CA secretion in bovine chromaffin cells (Uchiyama et al, 1994), and that the NO donor SNP enhances nicotine-induced CA secretion in cultured bovine chromaffin cells (O'Sullivan and Burgoyne, 1990). These findings suggest that NO may facilitate cholinergic agonistinduced CA secretion.…”
Section: Discussioncontrasting
confidence: 51%
“…Moreover, the presence of endothelial cells has been reported to inhibit the K + -induced or the nicotinic receptor agonist DMPP-induced CA secretion in cultured bovine chromaffin cells (Torres et al, 1994), suggesting that not only nNOS but also eNOS may play roles in modulating adrenal CA secretion. In contrast, it has been shown that L-NAME inhibits ACh-induced CA secretion in bovine chromaffin cells (Uchiyama et al, 1994), and that the NO donor SNP enhances nicotine-induced CA secretion in cultured bovine chromaffin cells (O'Sullivan and Burgoyne, 1990). These findings suggest that NO may facilitate cholinergic agonistinduced CA secretion.…”
Section: Discussioncontrasting
confidence: 51%
“…Moreover, the presence of endothelial cells has been reported to inhibit the K + -induced or the nicotinic receptor agonist DMPP-induced CA secretion in cultured bovine chromaffin cells (Torres et al, 1994), suggesting that not only nNOS but also eNOS may play roles in modulating adrenal CA secretion. On the contrary, it has been reported that L-NAME inhibits ACh-induced CA secretion in bovine chromaffin cells (Uchiyama et al, 1994) and that the NO donor SNP enhances nicotine-induced CA secretion in cultured bovine chromaffin cells (O'Sullivan and Burgoyne, 1990). These findings suggest that NO may facilitate cholinergic agonist-induced CA secretion.…”
Section: Discussioncontrasting
confidence: 48%
“…Thus, blockade by resveratrol of quantal release could be mediated by cGMP, although the role of this nucleotide in regulating catecholamine release is controversial. For instance, O'Sullivan and Burgoyne (1990) found that NO donors augmented catecholamine release. Others found inhibition of secretion (Oset-Gasque et al, 1994;Rodriguez-Pascual et al, 1996).…”
Section: Discussionmentioning
confidence: 99%